2007
DOI: 10.1007/s00442-007-0889-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of predator density on nonindependent effects of multiple predator species

Abstract: Interactions between multiple predator species are frequent in natural communities and can have important implications for shared prey survival. Predator density may be an important component of these interactions between predator species, as the frequency of interactions between species is largely determined by species density. Here we experimentally examine the importance of predator density for interactions between predator species and subsequent impacts on prey. We show that aggressive interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…3 Net biodiversity effect, complementarity effect, and selection effect from the additive partitioning analysis of fish growth in the mesocosms. Mean values of the biodiversity effects (卤 95% CL) are compared across fish species richness water use in grassland prairies (Verheyen et al 2008), capture efficiency of crabs in a marine inter-tidal food web (Griffen and Williamson 2008), and zooplankton grazing on algae in high nutrient concentrations (Dzialowski and Smith 2008). Our results support the theory of resource complementarity that predicts higher species diversity will capture a greater amount of resources and be more productive (Cardinale et al 2006).…”
Section: Discussionsupporting
confidence: 71%
“…3 Net biodiversity effect, complementarity effect, and selection effect from the additive partitioning analysis of fish growth in the mesocosms. Mean values of the biodiversity effects (卤 95% CL) are compared across fish species richness water use in grassland prairies (Verheyen et al 2008), capture efficiency of crabs in a marine inter-tidal food web (Griffen and Williamson 2008), and zooplankton grazing on algae in high nutrient concentrations (Dzialowski and Smith 2008). Our results support the theory of resource complementarity that predicts higher species diversity will capture a greater amount of resources and be more productive (Cardinale et al 2006).…”
Section: Discussionsupporting
confidence: 71%
“…Preliminary data indicated that mud crabs forage most actively at night. We therefore conducted all experimental trials at night under illumination from dim red lights to minimize disturbance of crabs (Griffen and Williamson 2008). We further ensured that observers did not disturb the crabs and alter behavior by placing the observer behind a screen made of black plastic.…”
Section: Refuge Use In the Presence And Absence Of Predator Cuesmentioning
confidence: 99%
“…Stachowicz. 3 E-mail: bgriffen@biol.sc.edu their strength and importance relative to other community-structuring factors. For example, recent studies demonstrate that TMII vary with such factors as habitat complexity (e.g., Griffen 2006, Grabowski et al 2008, resource identity (Trussell et al 2008), predator hunting mode (Schmitz and Suttle 2001), and species density (Griffen and Williamson 2008 One potentially contributing factor that has received broad attention outside the realm of TMII research is individual trait variation. Variation between individuals within a population is common for ecological traits, and recent reviews have highlighted this variation in numerous individual traits, including food and habitat preferences (Bolnick et al 2003), morphology (Bolnick et al 2007), physiology (Careau et al 2008), and behavior (Sih et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Strong interference effects that reduce mussel mortality (Griffen 2006;Griffen and Williamson 2008) were likely absent here because experiments were sufficiently long that mussel depletion could occur even at reduced predation rates (Fig. 1).…”
Section: Discussionmentioning
confidence: 93%